GENDER DIFFERENCES IN LEVELS OF TOXIC POSITIVITY IN ADOLESCENTS: A QUANTITATIVE STUDY - Putra, Rahman Pranovri; Ramadhanti, Auliya; Rizky, Deo Alfa (LPPM Universitas Jambi, 2023)
This research is the first research derived from applied science in the field of public health to explore gender differences in levels of toxic positivity in adolescents. Toxic positivity is defined as the overgeneralization and ineffectiveness of happy and optimistic states in all situations resulting in the denial, minimization, and invalidation of authentic human emotional experiences. The research sample consisted of male and female teenagers aged 18-24. Data was collected through a questionnaire that measures the level of toxic positivity based on responses related to positivity and behavior that can ignore or override negative emotions. The results show that there is a significant difference between male and female adolescents in the level of toxic positivity. Adolescent girls tend to show lower levels of toxic positivity than adolescent boys. These findings indicate that adolescent girls are more likely to acknowledge and manage their negative emotions more openly than adolescent boys. This study provides important insights into gender differences in the context of toxic positivity in adolescents. The results can be used to develop more targeted interventions and approaches to help adolescents manage their emotions healthily and constructively. The novelty of this research is that it introduces a new measure of toxic positivity that can capture the subtle and complex ways in which people cope with their emotions. This study also contributes to the literature on gender and emotion regulation by highlighting differences in patterns and consequences of toxic positivity among male and female adolescents.